Effect of financial ratios on the poultry's stock returns in Bursa Malaysia - Wong, Wei Kok (2018)
The purpose of this research is to investigate the performance of listed poultry firms in Bursa Malaysia during 2011 to 2016 by using financial statements analysis such as dividend yield (DY), return on assets (ROA), return on equity (ROE), debt equity ratio (DER) and current ratio (CR). The findings indicated that majority of poultry firms in Bursa Malaysia were performed well in terms of using their assets, debts and investment during 2011-2016. Next, this study also examine the relationship between financial ratios and stock returns in poultry industry by using multiple linear regression analysis. The results show that the selected financial ratios do not have significant impact to the stock return partially and simultaneously among the listed poultry firms in Bursa Malaysia.